Dealing with low‐probability shocks: The role of selected heuristics in farmers' risk management decisions. (2nd March 2023) - Duden, Christoph; Mußhoff, Oliver; Offermann, Frank
Abstract: Dealing with weather extremes is a major challenge for farmers and often comes at high costs for public budgets. Therefore, we investigate the influence of specific simplified decision rules, so‐called heuristics, on farmers' willingness to pay (WTP) for protecting themselves against low‐probability and high‐consequence weather shocks. To this end, we conducted a framed field experiment with 237 farmers in Germany, using incentivized lottery‐based multiple price lists. We explored the effects of different heuristics within the prospect theory framework. Our results indicate that, on average, farmers exhibit risk‐loving behavior towards monetary losses, leading to a low WTP for risk mitigation. The results also suggest that the imitation heuristic, shock experience heuristics, and the threshold of concern heuristic influence farmers' WTP. Farmers specifically imitate successful farmers when these are risk‐loving. The lack of personal experience with low‐probability events induces farmers to assign less weight to low‐probability shocks, which lowers their WTP. Farmers also systematically assign less weight to low‐probability shocks that they consider "too rare to be concerned about." Accounting for the use of these heuristics can help design improved risk management instruments and policies.